Shading Analysis For The Siting Of Solar Pv Power Plant - Vinodh, Annathurai; Gan, Chin Kim; Baharin, Kyairul Azmi; Ab Ghani, Mohd Ruddin (Asian Research Publishing Network (ARPN), 2016)
Solar Photovoltaic (PV) system is environmentally-friendly which could reduce the consumption of electricity from the non-renewable energy sources. However, the generation of the PV system is highly dependent on weather conditions. More specifically, the shading of PV modules is a common phenomenon which can affect the performance of the PV system. Hence, this paper aims to establish relationship between the distance of a PV plant from a building object and its associated height. To achieve this, the Solar Pro software is used to simulate the shading conditions and estimate the PV systems’s output. For validity, the data of PV energy, total irradiation, Peak Sun Hour and performance ratio obtained from the simulation were compared with the Meteonorm software. The findings from this research suggest the relative distance of a PV plant should be located in relationship to its nearest building object. It is expected that such findings will provide a good rule-of-thumb for the solar PV system designer in selecting the viable project site.